Generation of diffraction-free beams using resonant metasurfaces. (30th October 2020) - Bao, Rui; Mou, Zhen; Zhou, Changda; Bai, Qingwang; He, Xiaobo; Han, Zhanghua; Wang, Shuyun; Teng, Shuyun
Abstract: Several metasurface diffraction-free beam generators are designed by using a set of resonant V-shaped nanoholes. Cosine beams, Bessel beams and cosine Bessel beams are generated through the corresponding metasurface structures with V-shaped nanoholes arranged in different ways. Theoretical analysis provides the design mechanism for these diffraction-free beam generators, numerical simulations and experiment measurement give the powerful verification for the generation of diffraction-free beams. The proposed diffraction-free beam generators have advantages of ultra-thin thickness, compact structure, ease to manufacture and flexibility to operate. The generated diffraction-free beams show high efficiency, polarization independence and validity for any visible wavelength. The compact design is benefit to the applications of diffraction-free beams in nanometer fabrication, optical integrated imaging and optical micromanipulation.